Reliability based life cycle assessment for future solid waste management alternatives in Portugal. - Pires, Ana (The International Journal of Life Cycle Assessment)
Background, aim and scope This paper presents a study related to the application of the reliability based life cycle assessment (LCA) to assess different alternatives for solid waste management in the Setubal peninsula, Portugal. The current system includes waste collection, transport, sorting, recycling and mechanical and biological treatment (MBT) by means of aerobic treatment and landfill. In addition, some future expansion plans are discussed. Materials and methods The proposed 18 alternatives were examined with respect to six impact categories based on a customized life cycle inventory (LCI). All the alternatives are designed to comply with the targest prescribed in the Packaging and Packaging Waste Directive and the Landfill Directive. These 18 alternatives were eventually assessed by using the reliability based LCA methodology with respect to some uncertain parameters and scenarios. Results and discussion The results show that solutions based on anaerobic digestion at the MBT followed by energy recovery are the most advantageous options. Overall, recycling may help to avoid most environmental impacts. Alternatives which treat massively biodegradable municipal waste are also competitive. In addition to the recycling options, electricity production is also an influential determinant which affects the results. The uncertainty analysis focused on testing different energy from waste options (like landfill and MBT biogas electricity production) and different recycling substitution ratios. Such a quantitative analysis is proved effective to confirm the reliability of the LCi in the study. Conclusions In order to improve the sustainability of the solid waste management (SWM) system, final suggestions may concentrate on the closure of aerobic MBT, the enhancement of anaerobic digestion MBT treatment, and the maximization of energy recovery from high calorific fractions of the waste streams. However, the option of stabilized residue applications cannot be encouraged at this stage, especially due to the absence of Portuguese regulations to control the quality of organic products issuing from biological treatment units.